A comprehensive framework for studying migration policies (and a call to observe them beyond immigration to the West) - Luicy Pedroza (German Institute of Global and Area Studies (GIGA), 2020)
This piece is both an exercise in critical conceptual landscaping in the field of Migration Studies and the proposal of an analytical framework that can correct some of its most serious biases. The framework I propose allows the observing of migration policies as if they constituted a comprehensive policy field. This will permit comparisons across the whole spectrum of migration policies on a rigorous basis, and for all countries and regions. I identify two constitutive sides to the proposed framework, each dealing with how state-like polities regulate the mobility of incoming or outgoing persons. I further suggest that it include regulations on the rights of individuals to pass through three stages of any international migration journey: the right to enter/exit; the rights as immigrant residents/emigrant non-residents; and, the rights to citizenship and nationality. This comprehensive framework for studying migration policy promises advances for empirical agendas, but also for connecting them to normative ones rooted in global justice and democratic concerns.
Keywords: 300; migration; policy; emigration; diaspora; integration; citizenship; coherence